Pobór, wcielenie, „pruska dyscyplina”, dezercje. Wstęp do badań nad historią społeczną służby wojskowej w stalinowskiej Polsce (1950–1955) - Jarosz, Dariusz; Miernik, Grzegorz (Polska 1944/45-1989. Studia i Materiały, 2019)
Artykuł zawiera próbę wstępnej analizy wybranych zagadnień służby wojskowej w Polsce w latach 1950–1955. Autorzy próbują to uczynić przy zastosowaniu metodologii historii społecznej. Przedmiotem ich zainteresowania są: pobór i wcielenie do wojska, szykany, represje i nieregulaminowe kary stosowane wobec żołnierzy w jednostkach wojskowych (nazywane wówczas „pruską dyscypliną”) oraz zjawisko dezercji (definicje, legislacja, skala, przyczyny). Podstawę ustaleń stanowią przede wszystkim wojskowe dokumenty archiwalne. Conscription, incorporation, “Prussian drill”, desertions: an introduction to the research into the social history of military service in Stalinist Poland (1950–1955) An analysis of military files reveals that in the Stalinist period the mandatory military service was a mass social experience which abounded with conflicts and tensions. The conscription itself, and then the enlistment were conducive to the use of various social strategies that were to preserve young men from serving in the army. These efforts were often supported by their workplaces which appealed for a deferment for their employees necessary for the realization of their production plans. One of the main problems of everyday operations of military troops in Stalinist Poland was the prevalence of socially pathological phenomena. Both the regular officers and senior privateers subjected the young soldiers to harsh and even cruel treatment. This behaviour, involving harassment and persecution unrelated to the service, was termed the “Prussian drill”, and was officially condemned, although it was applied. Military sources contain descriptions of some cases, but it is impossible to establish their actual number. Conditions of military service in the Stalinist period, including cases of Prussian drill, were one of many reasons of some “extraordinary cases”, including desertions. Desertions were among three most frequent extraordinary cases (besides accidents of mechanical vehicles and unfortunate accidents) in the Polish People’s Army in the first half of the 1950s. Usually, they were caused by soldiers most freshly conscripted, who most badly tolerated not only persecutions but also separation from their home and family. Their relatively large number resulted also from a broad definition of desertion adopted in the contemporary law regulations that included acts by which a soldier did not seek to permanently abandon and forsake his duty of military service.